2008
DOI: 10.1089/jir.2007.0110
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Herpes Simplex Virus Type 1 in the Anterior Segment of the Eye Is Linked to a Deficiency in NK Cell Infiltration in Mice Deficient in CXCR3

Abstract: In response to ocular herpes simplex virus type 1 (HSV-1) infection in mice a rapid induction or increase in the local expression of chemokines including CXCL10 is found. The present study investigated the role of the receptor for CXCL10, CXCR3, in the host response to corneal HSV-1 infection. Mice deficient in CXCR3 (CXCR3−/ −) were found to have an increase in infectious virus in the anterior segment of the eye by day 7 post infection. Coinciding with the increase, selective chemokines including CCL2, CCL3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…The absence of tumor-infiltrating NK and NKT cells is the likely reason for the enhanced tumor growth and shorter median survival time in the tumor-bearing CXCR3-deficient animals. The reduction of NK and NKT cells in CXCR3-deficient mice has also been documented in ocular herpes simplex virus type 1 infection (38) as well as pulmonary fibrosis (39). However, it has been reported that CXCR3-deficiency results in an impaired homeostasis of NK and NKT cells, with unchallenged CXCR3-deficient mice having significantly reduced numbers of NK and NKT cells in lung, liver and peripheral blood (39).…”
Section: Discussionmentioning
confidence: 98%
“…The absence of tumor-infiltrating NK and NKT cells is the likely reason for the enhanced tumor growth and shorter median survival time in the tumor-bearing CXCR3-deficient animals. The reduction of NK and NKT cells in CXCR3-deficient mice has also been documented in ocular herpes simplex virus type 1 infection (38) as well as pulmonary fibrosis (39). However, it has been reported that CXCR3-deficiency results in an impaired homeostasis of NK and NKT cells, with unchallenged CXCR3-deficient mice having significantly reduced numbers of NK and NKT cells in lung, liver and peripheral blood (39).…”
Section: Discussionmentioning
confidence: 98%
“…Now the role of NK cells has been defined in virus infections such as human cytomegalovirus (8,11,55), murine cytomegalovirus virus (2,32), influenza virus (28,35), herpes simplex virus (44,52), ectromelia virus (16,41), and human immunodeficiency virus (HIV) (14,50,56). In two of these infections, a lack or deficiency in NK cell function leads to increased susceptibility to infection (6,10).…”
mentioning
confidence: 99%
“…Studies using animal models of virus infection, such as herpes simplex virus infection, have indicated that these chemokine receptors are involved in NK cell trafficking to the ocular surface, lung, and genital mucosa. [28][29][30] The drastic change in NK cell types effectively dampens the antiviral response in situ because the licensed, mature CD56 dim NKG2A À NK cells that are capable of responding against adenovirus-infected epithelial cells are replaced by the hyporesponsive CD56 bright NK cells and NKG2A þ CD56 dim NK cells. An important cell-contact factor affecting anti-HAdV NK cell responses is the upregulation of HLA-E and the downregulation of HLA-A/B/C expression.…”
Section: Discussionmentioning
confidence: 99%